Fe(III)-Citrate-Complex-Induced Photooxidation of 3-Methylphenol in Aqueous Solution - N. Seraghni; S. Belattar; Y. Mameri; N. Debbache; T. Sehili (International Journal of Photoenergy)
The photodegradation process of m-cresol (3-methylphenol), induced by Fe(III)-Cit complex, was investigated upon irradiation at 365 nm in natural water. The composition and photochemical properties of Fe(III)-Cit complex were studied by UV-Visible absorption spectrophotometer for optimizing the stoichiometry of the complex and photolysis under irradiation at 365 nm, respectively. A dark investigation of the system was performed before studying the photochemical behavior. The photooxidation efficiencies of m-cresol were dependent on the pH value, optimized at pH 2.86, oxygen, initial concentrations of Fe(III)-Cit complex, and m-cresol. Additionally, to look into the mechanism of m-cresol degradation using Fe(III)-Cit, tertiobutanol alcohol was used as scavenger for hydroxyl radicals and the result suggested that hydroxyl radical attack was the main pathway of m-cresol degradation. Besides, oxygen can enhance the photolysis of Fe(III)-Citrate complex by trapping the electron on the carbon centered radical formed after the photoredox process. Then O2•− formed reacts rapidly leading finally to formation of •OH radical. In absence of oxygen, less reactive species are formed; consequently the disappearance of m-cresol was strongly inhibited. Our work shows that the presence of Fe(III)-Citrate complex could have a considerable impact on the fate of organic pollutant in aquatic environment.